Morphological peculiarities of aorta and pulmonary artery in newborns after acute postnatal hypoxia in experiment. - Markovskyi, V. D.; Zvierieva, I. S. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Intrauterine hypoxia of fetus and newborn asphyxia occupy one of the first places in the structure of perinatal morbidity and mortality, and reach 67.0% and 43.0%, respectively. The endured hypoxia decreases adaptive opportunities of the child’s organism with negative effect on all organs and systems, including cardiovascular system affected in this pathological condition in 40-70 % cases. Objective. The aim of research is to make comparative analysis of the pathomorphological features of the pulmonary artery and aorta of newborn rats with acute postnatal hypoxia in experiment. Methods. Our experimental research on modeling acute postnatal hypoxia was performed on laboratory rats line WAG. Pregnant rats were not exposed to oxygen starvation, however, their descendants were exposed to alpine hypoxia corresponding to elevation of 7,500 meters for 20 minutes one time in the first 24 hours of life, and then were removed from the experiment. The resulting material was subjected to macroscopic, microscopic, morphometric methods of investigation. Results. Macroscopic examination of the pulmonary artery and aorta was carried out with a magnifier (×3, 8 diopters). Both vessels were elastic with smooth inner membrane. Microscopically, the wall of the pulmonary artery, as well as the aorta, consisted of three membranes – internal (tunica intima), medium (tunica media), and external (tunica adventitia). Indexes of the relative volume of tunica intima and media of the aorta decreased significantly relative to the pulmonary artery, and the volumes of tunica adventitia increased, most likely because of edema caused by increased vascular permeability due to hypoxia. The findings can be associated with activation of fibulin, fibrillin and emilin proteins what are responsible for these fibers formation. Violation of elastic and collagen fibers ratio in the aorta, towards the latter, decreases vessel elastic properties. The adventitial membrane of both vessels is edematous, with signs of sclerotic changes. It is formed by collagen and elastic fibers, full-blooded vasa vasorum, lymphatic vessels, without degenerative signs in nervi vasorum. Conclusion. Morphological signs of endothelial dysfunction were observed in the pulmonary artery and in the aorta of newborns with acute postnatal hypoxia. There is disturbance in the ratio of the elastic and collagen fibers in the aorta toward the second one under the acute postnatal hypoxia influence, what deteriorates the elastic vessel wall properties. On the contrary, elastic fibers predominate in the pulmonary artery. It can be related to activation of proteins what are responsible for these fibers formation. Thus, the carried out experiment demostrated significant pathomorphological changes in the pulmonary artery and aorta, what can lead to vascular pathology in future.